Effects of Kinetin and Root Tip Removal on Exudation and Potassium (Rubidium) Transport in Roots of Honey Locust - Hong, Sung Gak (1976)
Exudation, (86)Rb transport, and water permeability were examined in excised roots of honey locust (Gleditsia triacanthos L.) treated by removing the tip 2 mm (tip-cut 2 mm) or tip 8 mm of the root, or by adding kinetin, or by both treatments. Tip removal increased the rate of exudation. Kinetin, 5 × 10(−6)m, inhibited exudation and Rb transport in tip-cut 2-mm roots; the inhibition was reversible. Kinetin inhibition of exudation was initially associated with lower K(Rb) transport and later with decreases in both ion transport and water permeability. Exudation was also inhibited at 10(−10) to 10(−7)m kinetin. Exudation from roots with intact tips was not altered by kinetin until after about 24 hours. Light during the exudation period had no significant (95%) influence on rate of exudation during the first 24 hours whether root tips were cut or kinetin applied. The results suggest the involvement of the root tip in regulating exudation in other parts of the root. This regulation might occur through cytokinin control of water permeability and the rate of ion transport.